2000
DOI: 10.1023/a:1008352726155
|View full text |Cite
|
Sign up to set email alerts
|

Relapses of childhood anaplastic large-cell lymphoma: Treatment results in a series of 41 children - a report from the French Society of Pediatric Oncology

Abstract: Relapsed ALCL are highly chemosensitive but over 40% of the patients experience several relapses. Prolonged conventional chemotherapy based on vinblastine might, in some cases, be as efficient as short intensive treatment with ABMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
145
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 29 publications
10
145
0
6
Order By: Relevance
“…38,42 Poor prognostic features have been defined as (1) a delayed or partial response to first-line therapy, 13,22,43 (2) central nervous system or BM involvement at presentation 35 or (3) time to relapse from initial diagnosis. 44 Bureo et al 35 reported an expected EFS of 82.5% in a small group (n ¼ 13) of high-risk patients with these poor prognostic features who were consolidated with high-dose therapy followed by AutoSCT in CR1 (Table 1). The European Group for Blood and Marrow Transplantation (EBMT), also in a retrospective review of adult and pediatric patients with ALCL, point out that those patients transplanted in CR1 had improved survival compared to those patients who received AutoSCT in CR2, partial response or sensitive relapse.…”
Section: Nhlmentioning
confidence: 99%
See 1 more Smart Citation
“…38,42 Poor prognostic features have been defined as (1) a delayed or partial response to first-line therapy, 13,22,43 (2) central nervous system or BM involvement at presentation 35 or (3) time to relapse from initial diagnosis. 44 Bureo et al 35 reported an expected EFS of 82.5% in a small group (n ¼ 13) of high-risk patients with these poor prognostic features who were consolidated with high-dose therapy followed by AutoSCT in CR1 (Table 1). The European Group for Blood and Marrow Transplantation (EBMT), also in a retrospective review of adult and pediatric patients with ALCL, point out that those patients transplanted in CR1 had improved survival compared to those patients who received AutoSCT in CR2, partial response or sensitive relapse.…”
Section: Nhlmentioning
confidence: 99%
“…The prognosis for children who develop progressive or recurrent disease is poor with o50% DFS. 44 The EBMT reported their results of AutoSCT in 64 adult and pediatric patients with T-and null-cell CD30 þ ALCL (Table 1). 41 In this series, the group who consistently benefited from high-dose therapy and AutoSCT were the patients with poor prognostic features who were The Berlin-Frankfurt-Mu¨nster (BFM) group recently reported on the feasibility and efficacy of intensive reinduction therapy followed by AutoSCT or AlloSCT in children and adolescents with relapsed ALCL after BFM frontline therapy.…”
Section: Alclmentioning
confidence: 99%
“…Compared with ALK-negative (ALKÀ) ALCL, ALK þ ALCL have a better prognosis when undergoing CHOP-based chemotherapy, 21,22 however, ALK þ ALCL relapses after chemotherapy are very invasive and have a worse prognosis. 23,24 We recently developed conditional mouse models for NPM-and TPM3-ALKinduced lymphomagenesis using the tetracycline system.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде экспериментальных работ было показано, что Ara-GTP более активно накапливается в Т-клетках, чем в В-клетках [13]. Применение нела-рабина при лечении рецидивов/рефрактерных форм Т-ЛБЛ позволило достичь полных ремиссий (ПР) лишь в 13 % [14].…”
unclassified
“…При оценке влияния ТКМ на конечные результаты терапии было установлено, что ТКМ не сильно превосходит эффект программной ПХТ. Интересно заметить, что при рецидиве после ТКМ возможно получение ремис-сий на курсах, включающих еженедельное введение винбластина [14]. Факторами, определяющими высо-кий риск неудачи терапии являются поражение вну-тренних органов, вовлечение средостения и уровень ЛДГ более 800 ЕД/л.…”
unclassified